2022
DOI: 10.1126/sciadv.abn8241
|View full text |Cite
|
Sign up to set email alerts
|

Rapid liquid phase–assisted ultrahigh-temperature sintering of high-entropy ceramic composites

Abstract: High-entropy ceramics and their composites display high mechanical strength and attractive high-temperature stabilities. However, properties like strong covalent bond character and low self-diffusion coefficients make them difficult to get sintered, limiting their mass popularity. Here, we present a rapid liquid phase–assisted ultrahigh-temperature sintering strategy and use high-entropy metal diboride/boron carbide composite as a proof of concept. We use a carbon-based heater to fast-heat the composite to aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…In the overdamping test, a 150 Ω resistor is applied and the discharge current waveform of BNST-CLT is shown in Figure 6c. According to this, the discharge energy storage density W d could be derived from the following equation [53] W d = R ∫ I(t) 2 dt∕V (6) in which R stands for the applied resistance of 150 Ω, and I, t denotes the discharge current as well as time, correspondingly. The W d achieves 1.01 J cm −3 at an electric field of 200 kV cm −1 (Figure 7d), which is closely in line with the ferroelectric test results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the overdamping test, a 150 Ω resistor is applied and the discharge current waveform of BNST-CLT is shown in Figure 6c. According to this, the discharge energy storage density W d could be derived from the following equation [53] W d = R ∫ I(t) 2 dt∕V (6) in which R stands for the applied resistance of 150 Ω, and I, t denotes the discharge current as well as time, correspondingly. The W d achieves 1.01 J cm −3 at an electric field of 200 kV cm −1 (Figure 7d), which is closely in line with the ferroelectric test results.…”
Section: Resultsmentioning
confidence: 99%
“…[4,5] Superior to others, ceramic capacitors represent the mainstream choice since there are the advantages of superior dielectric properties along with high temperature resistance. [6] However, the restricted energy storage density of dielectric capacitors compared to electrochemical capacitors constrains the further adoption. [2,7] Enhancing the energy storage performance of dielectric capacitors has emerged as a current research priority.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-entropy compounds (HECs) have gained extensive attention in recent years due to their unconventional structures and remarkable physicochemical properties. Typically composed of five or more near-equimolar principal metal cations within a solid-solution phase, HECs exhibit a high degree of disorder in their atomic arrangements, resulting in increased configurational entropy. Consequently, it becomes difficult to regulate the structure and morphology of HECs during their synthesis, particularly when their size is reduced to the nanoscale or even smaller, such as the subnanoscale. …”
Section: Introductionmentioning
confidence: 99%
“…The decrease of energy thermodynamically is beneficial to overcoming elemental immiscibility to form a high-entropy state. , Recently, we reported that utilizing Ga with relatively negative mixing enthalpy to reduce Gibbs free energy can realize uniform elemental mixing in high-entropy alloys under relatively mild reaction conditions . Therefore, it provides an idea to construct a high-entropy mixing state in oxides.…”
mentioning
confidence: 99%